Digital citizen empowerment: A systematic literature review of theories and development models. Issue 4 (2nd October 2022) - Sharma, Swapnil; Kar, Arpan K.; Gupta, M. P.; Dwivedi, Yogesh K.; Janssen, Marijn
ABSTRACT: Governments worldwide invest heavily in digital initiatives to develop information societies with connected and actively engaged citizens, but problems like lacking sustained engagement and quality of participation still plague them. We undertook a systematised literature review on the Scopus and Web of Science (WoS) databases, covering dispersed literature surrounding Digital Citizen Empowerment (DCE) from the past two decades.Categorising the literature under four thematic categories or strategies of DCE: Digital Activism (DA), Multi-channel Service Delivery (MCSD), Participatory Budgeting (PB), and Deliberative Governance (DG) critical comparative analysis is done. A conceptual model of DCE, covering how theories from different inter-disciplinary areas of political, social, and information science influence the development of information societies and DCE is presented. Action points in our conceptual model are mapped to policy objectives targeting improved delivery of empowering policy goals by practitioners, and future research opportunities in the context of DCE are discussed.